Globalization and a welfare program for the marginalized - Udo Broll; Alexander Kemnitz; Vivekananda Mukherjee (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2009)
We study the economic relationship between globalization and inequality within a country. In a partial equilibrium it is shown even when the local government exclusively maximizes the welfare of the marginalized (unemployed) people, relative consumption inequality between employed and the marginalized always rises by intensified globalization. However in certain situations the relative income inequality may fall.
Keywords: I30; O15; O19; F42; 330; Globalization; inequality; marginalization; policy